Desain Cetakan Plastik Pot dan Tatakan Pot Tanaman Menggunakan Software Autodesk Pada Mesin Injection Moulding - Esti Taqwaningrum; Kardiman Kardiman; Deri Teguh Santoso (Peneliti.net, 2022)
Plastic is one of the most widely used materials in the world, almost all products we find use plastic. There are several plastic material processing processes, one of which uses the injection molding method which is one of the important technologies used to produce various product. The purpose of this research is to design a product of mold design for pots and placemats using computer aided design (CAD) software and simulations performed on solidworks software. The results of this study are based on confidence with a 95% confidence level, the average confirmation experimental value is in the confidence interval range with the simulation results still not stable because they still have a few product defects, one of which is the air trap